Infectious Agents Causing Abortion Among Pregnant Women : An Article Review - Al-ma’amouri, May Y. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Background: Abortion is a spontaneous loss of pregnancy before 20 weeks. Approximately 42 million pregnancies end in abortion. The maternal infections that are transmissible from mother to fetus are caused by many pathogens, of which the TORCH complex contributes majorly to neonatal and infant deaths globally. The aim of this study is to identify the prevalence and types of infectious causes of abortion, modes of transmission, and methods of prevention and treatment. Conclusions: abortion occurs during the first three months of pregnancy and is due to several reasons, including infection during pregnancy. This infection affects the pregnancy and causes many health problems for the mother and fetus that lead to abortion.